7-Chloro-4-[(E)-N′-(4-fluorobenzylidene)hydrazinyl]quinoline monohydrate - de Souza, Marcus V. N. (International Union of Crystallography, 2009)
The molecule of the title hydrate, C(16)H(11)ClFN(3)·H(2)O, is slightly twisted, as indicated by the dihedral angle of 9.55 (10)° formed between the quinoline ring system and the benzene ring. The conformation about the C=N double bond is E, and the amine-H atom is oriented towards the quinoline residue. In the crystal structure, the water molecule accepts an N—H⋯O and makes two O—H⋯N(quinoline) hydrogen bonds, generating a two-dimensional array in the ab plane, which is further stabilized by C—H⋯O interactions. The most significant contacts between layers are of the type C—H⋯F.